LOCAL AUTONOMY LAW EFFECTS ON ADMINISTRATIVE AND FINANCIAL STRUCTURE OF LOCAL GOVERNMENTS IN JAPAN - YILMAZ, NESLİHAN and ÖNEZ ÇETİN, ZUHAL (Ecoforum Journal, 2017)
The local governments that have a significant pie within the central government expenditure furnished with vital responsibilities by the central government concerning the provision of the public services. Within the framework of the applications towards financial autonomy; the development of financial policies take attention in related with the stability of the responsibility and its financial share, and as a result of that, some reform implementations come to the front side. The continuously increasing budget deficit and the expected alterations at the fiscal federalism application field before the local government reform process do not abolish entirely to the dependency of local government to the central administration but reduce this dependency to a great extent. The local autonomy that was enforced in 2000, the limits of local autonomy that is attributed from the central government to the local governments revised and a large-scale and persistent proves of change is foreseen for the provision of the effectiveness at the regional scale. In this regard, some regulations come forefront having ties to strengthen local community and governance approach. In this study, the first objective is examining the administrative framework of the local governments in Japan before the enforcement of the Local Autonomy Law for grasping the main differences after the implementation of that related Law. The second target is analyzing deeply the Local Autonomy Law in related with the administrative and financially updated items. The third objective is putting forth reflections and effects of that related Law on the transformation of the financial structure of the local governments in Japan.